Clinical effects and mechanisms of a Chinese patent medicine, Tongxinluo capsule, as an adjuvant treatment in coronary heart disease - Jing Wang; Tian Li Li; Pei Fen Chang; Yu Qian Gao; Jia Sai Fan; Chen Hao Zhang; Hai Yan Zhu (Heliyon, 2024)
Coronary heart disease (CHD) is the leading cause of death globally, posing a serious threat to human health. However, the current treatment approaches available for CHD fall short of the ideal results. Tongxinluo (TXL) is a traditional Chinese medicine (TCM) that has been employed in the clinical treatment of cardiovascular and cerebrovascular diseases (such as angina pectoris, stroke, etc.) in China for many years and holds great potential as a prospective treatment. TXL either as a standalone treatment or in combination with interventions recommended in CHD guidelines has been shown to be effective and well tolerated in clinical trials for CHD. Drawing on the evidence from clinical trials and experimental studies, this review will focus on the cardiovascular protective properties and related mechanisms of TXL. By searching 8 Chinese and English databases, more than 4000 articles were retrieved. These articles were categorized, then read, and finally written into this review. In this review, the pharmacological properties of TXL include regulation of blood lipids, improvement of endothelial function, anti-inflammatory, antioxidant, inhibition of apoptosis and regulation of autophagy, anti-fibrosis, promotion of angiogenesis, and modulation of exosome communication. The information provided in this review will help the reader to comprehend better the insights that TCM has developed over time in practice and provide new perspectives for the treatment of CHD.